Looking for the missing rich: Tracing the top tail of the wealth distribution - Stefan Bach; Andreas Thiemann; Aline Zucco (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
We analyze the top tail of the wealth distribution in Germany, France, and Spain based on the first and second wave of the Household Finance and Consumption Survey (HFCS). Since top wealth is likely to be underrepresented in household surveys, we integrate big fortunes from rich lists, estimate a Pareto distribution, and impute the missing rich. In addition to the Forbes list, we rely on national rich lists since they represent a broader base for the big fortunes in those countries. As a result, the top percentile share of household wealth in Germany jumps up from 24 percent to 31 percent in the first and from 24 to 33 percent in the second wave after top wealth imputation. For France and Spain, we find only a small effect of the imputation since rich households are better captured in the survey.
Keywords: D31; C46; C81; 330; wealth distribution; missing rich; Pareto distribution; HFCS